Demise of Kreutz Sungrazing Comet C/2024 S1 (ATLAS) - David Jewitt; Jane Luu; Jing Li (The Astronomical Journal)
Most Kreutz family sungrazing comets are discovered only days before perihelion, severely limiting observational opportunities to study their physical nature and decay. Kreutz sungrazer C/2024 S1 (ATLAS) was discovered a month before reaching its perihelion distance of 0.008 au, allowing physical observations from both ground- and space-based telescopes. We present observations from 0.9 to 0.4 au using the Nordic Optical Telescope showing that (1) nucleus disintegration was ongoing already at 0.7 au pre-perihelion, (2) the activity varied unpredictably with distance, and (3) the nucleus radius was  <600 m (red geometric albedo 0.04 assumed). We also use coronagraphic observations from the STEREO-A spacecraft to study C/2024 S1 at heliocentric distances  ≲ 0.1 au. We find that the coma scattering cross section peaked near 0.075 au and faded progressively, by a factor  ∼20, toward the last observation at 0.02 au. We interpret the near-perihelion fading as a result of the sublimation of refractory coma grains, beginning at blackbody temperatures  ∼1000 K, consistent with olivine composition. The comet was not detected after perihelion. We consider processes operating to destroy the nucleus when near perihelion, concluding that rotational instability and sublimation losses work together toward this end, even before entry of the comet into the Roche lobe of the Sun.